Adjusting supply chain involvement in countries with politician turnover: A contingency framework - Dong, Maggie Chuoyan; Huang, Qianqian; Liu, Zhiqiang (Journal of Operations Management, 2022)
Although the supply chain (SC) literature has discussed the influence of the political environment on global SC decisions, the role of political leaders has been overlooked. To fill this research void, we predict and show that the turnover of a country's top political leader (hereafter, “politician turnover”) increases policy uncertainty in the country, which drives multinational corporations (MNCs) to adjust their SC involvement there. We also identify three politician‐related contingency factors: the market‐friendliness of the successor relative to the incumbent, the length of the successor's political career, and corruption in the turnover country. In an analysis of politician turnover events from 2003 to 2018 and the global supplier‐customer relationships of US‐incorporated MNCs, we find that politician turnover causes MNCs to reduce SC involvement (measured as the proportions of an MNC's customers, suppliers, and the transaction volume that are located in the turnover country). The negative effect of politician turnover on SC involvement is exacerbated by corruption in the turnover country, mitigated when the successor has a long political career, and exacerbated when the successor is less market‐friendly than the incumbent; the effect becomes positive when the successor is more market‐friendly than the incumbent.